Improving Science Education Through New Perspectives - Kakiuthi, Andre [UNESP]; Matsuyama, Rafael Tsuji; Pimentel, Fernando Pisani [UNESP]; Martins de Moraes, Thiago Matheus [UNESP]; IEEE (Ieee, 2014)
The demand for engineers has always been high in growing countries, however, the world's seventh largest economy, Brazil, is still far from being one of the places with highest development in engineering. Through the normal curricula, high school students often learn theory only and investment is not made in the practical part, as a consequence the interest in engineering is low. Creating a design focused on the practical application of basic concepts of mathematics, physics and chemistry using simple materials and with an easy access to high school students is really important, as the goal is to get them interested in the field of science and technology and this action will improve their quality of life. The motivation and realization of an engineer will cause changes to society. The development of humanitarian engineering projects can help in the reduction of the number of social problems such as slums, sanitary issues which are very common in global cities like Sao Paulo and Rio de Janeiro - and water shortage - this kind of problem happens in cities located in the Brazilian Northeast Region - as there isn't a proper water distribution system.
Keywords: Education; Volunteer; Project; Engineering; Humanitarian